Art-based methods for Participatory Action Research (PAR). Issue 1 (1st April 2020) - Kunt, Zeynep
By reflecting on alternative forms of knowledge co-production through art-based methods, the article discusses the potential of Participatory Action Research (PAR) as a responsive research praxis. Art-based methods have widely been used in research engaging communities through giving access to the worlds of participants. At the intersections of disciplines, benefiting from a range of art forms from photography to theatre, this approach provides the space and tools for the exploration of multiple perspectives about shared problems or questions. In this respect, PAR is a significant methodology for communication studies with its alternative ways of knowledge production by positioning 'dialogue' and 'participation' at the centre.